Single brain metastases – prognostic factors and impact of residual tumor burden on overall survival - Baumgart, Lea; Anetsberger, Aida; Aftahy, Amir Kaywan; Wiestler, Benedikt; Bernhardt, Denise; Combs, Stephanie E.; Meyer, Hanno S.; Schneider, Gerhard; Meyer, Bernhard; Gempt, Jens (Frontiers in Oncology, 2024)
Brain metastases (BM) are a common and challenging issue, with their incidence on the rise due to advancements in systemic therapies and increased patient survival. Most patients present with single BM, some of them without any further extracranial metastasis(solitary BM). The significance of postoperative intracranial tumor volume in the treatment of singular/solitary BM is still debated.This study aimed to determine the impact of resection and postoperative tumor burden on overall survival(OS) in patients with single BM.Patients with surgically treated single BM between 04/2007-01/2020 were retrospectively included. Residual tumor burden(RTB) was determined by manual segmentation of early postoperative MRI(72h). Survival analyses were performed using Kaplan-Meier estimates for univariate analysis and Cox regression proportional hazards model for multivariate analysis, using preoperative KPSS,age,sex,RTB, incomplete resection and singular/solitary BM as covariates. 340 patients were included, median age 64 years(54-71). 119 patients(35%) had solitary BM, 221(65%) singular BM. Complete resection(RTB=0) was achieved in 73%, median preoperative tumor burden was 11.2 cm3(5-25), and RTB:0 cm3(0-0.2).Median OS of patients with singular BM was 13 months(4-33) vs 20 months(5-92) for solitary BM; p=0.062. Multivariate analysis revealed singular BM as independent risk factor for poorer OS: HR 1.840, p=0.005. Complete vs. incomplete resection showed no significant OS difference (13 vs. 13 months, p=0.737). When focusing on solitary BM, complete resection led to a longer OS(21 vs. 8 months), without statistical significance(p=0.250). Achieving RTB=0 resulted in higher OS for patients with solitary BM compared to singular BM(21vs.12 months,p=0.027). Patients who received postoperative radiotherapy (RT) had significantly longer OS compared to those without it(14vs.4 months, p<0.001), with favorable OS for stereotactic radiosurgery (SRS)(15 months(3-42),p<0.001) or hypofractionated-stereotactic radiotherapy (HSRT).When complete intracranial tumor resection is achieved, patients with solitary BM have a favorable outcome compared to singular BM. There is a strong presumption that complete resection leads to an improved oncological prognosis. Patients with solitary BM tend to benefit with a favorable outcome following complete resection. Hence, surgical resection should be considered as a treatment option for patients with either no or minimal extracranial disease. The highly favorable impact of postoperative RT on OS was demonstrated and confirmed, especially with SRS or HSRT.